2005
DOI: 10.1124/dmd.105.006486
|View full text |Cite
|
Sign up to set email alerts
|

Transient Inhibition of Cyp3a in Rats by Star Fruit Juice

Abstract: ABSTRACT:Star fruit juice is a potent in vitro inhibitor of CYP3A; however, few reports are available on the inhibition of CYP3A activities by star fruit juice in vivo. Therefore, in this study, we investigated the CYP3A-mediated star fruit-drug interaction in vivo. The effect of star fruit juice on carbamazepine pharmacokinetics was examined in rats. In comparison with water, the area under the concentration-time curve (AUC) of carbamazepine was approximately 1.3-fold greater when star fruit juice (2 ml) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
0
11
0
8
Order By: Relevance
“…Previous studies have suggested that star fruit juice, similar to grapefruit juice, might contain some compounds that are CYP inhibitors (3,4,6). These compounds have not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have suggested that star fruit juice, similar to grapefruit juice, might contain some compounds that are CYP inhibitors (3,4,6). These compounds have not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo evidence also suggested that star fruit juice inhibited the activity of CYP3A in rats (4). Compared to the control, the area under the concentration-time curve of carbamazepine (a typical CYP3A substrate) increased 1.3-fold following 2 mL star fruit juice administration (4). This indicated that FDI could occur in humans when star fruit juice is co-administered with drugs containing CYP3A substrates.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations